Changes in blood biochemical and enzyme profile in experimental chronic selenosis in buffalo calves (Bubalus bubalis)* - SINGH, RATTANDEEP; RANDHAWA, S S; DHILLON, K S (The Indian Journal of Animal Sciences, 2014)
Blood glucose, plasma biochemicals, viz. plasma urea nitrogen, creatinine, total proteins and albumin; and plasma enzymes activities, viz. alkaline phosphatase (ALP), alanine transferase (AL T) and aspartate transferase (AST) were analysed in buffalo calves after induction of selenosis by ad lib. feeding of selenium enriched (S.54 ppm) wheat straw for 84 days. The mean blood glucose values (48.70±1.45 mg/dl) reflected hypoglycaemia, whereas mean ALP (90.72±6.98 lU/L), ALT (43.5 1± 1.62 IU/L), AST (89.67±0.30 IU/L) activities and plasma urea nitrogen (13.08±0.69 mg/dl) showed significant increase after 14, 70, 56, 42, and 42 days, respectively, of feeding wheat straw, indicating chronic liver damage and nephritis respectively. However, mean plasma creatinine, total plasma proteins and albumin revealed nonsignificant alterations throughout the period of induction of selenosis as compared to respective mean values of healthy controls.